Pomological and biochemical peculiarities of peach hybrids and varieties for genus Persica Mill. (Prunus persica Borkh.) with anthocyanidin Persica vulgaris Mill, pigmentation of fruits pulp and leaves - О. О. Ріхтер; Є. П. Шоферістов (Plant Varieties Studying and Protection)
The chemical composition and the links between different groups of substances (content of dry substances, monosaccharides, saccharose, sum of sugars, titratable acids, proanthocyanidins, anthocyanidins, water soluble pectine, protopectin, sum of pectines and sugar-acid index) have been studied in hybrids fruits of Persica vulgaris Mill, subsp. erytrocarpa Zajats and Persica vulgaris Mill, subsp. atropurpurea (Schneid.) Zajats. The obtained data were compared with the characteristics typical for fruits of P. vulgaris Mill, subsp. nectarina (Ait.) Shof. and P. vulgaris Mill. Brief information about the biology of obtained distant hybrids forms have been given. The content of anthocyanine pigments (Cy-3-Glu, Cy-3- Ara, Cy-3-(6-Kum)- Glu) in fruits and leaves of different taxons for genus Persica Mill, has been analysed.